Estimating slug liquid holdup in high viscosity oil-gas two-phase flow. (March 2019) - Archibong-Eso, A.; Okeke, N.E.; Baba, Y.; Aliyu, A.M.; Lao, L.; Yeung, H.
Abstract: Slug flow is one of the most critical and often encountered flow patterns in the oil and gas industry. It is characterised by intermittency which results in large fluctuations in liquid holdup and pressure gradient. A proper understanding of its parameters (such as slug holdup) is essential in the design of transport facilities (e.g. pipelines) and process equipment (slug catchers, separators etc.). In this paper, experimental investigation of slug liquid holdup (defined as the liquid volume fraction in the slug body of a slug unit) is performed. Mineral oil with viscosity, μ = − 0.0043 T 3 + 0.0389 T 2 − 1.4174 T + 18.141 and air were used as test fluids. A 0.0254 m and 0.0762 m pipe internal diameters facilities with pipe lengths of 5.5 and 17 m respectively were used in the study. Electrical Capacitance Tomography was used for slug holdup measurements. Results obtained in the study shows that slug liquid holdup varied directly as the viscosity and inversely as the gas input fraction. Existing slug holdup correlations and models in literature did not sufficiently predict present experimental results. A new empirical predictive correlation for estimating slug liquid holdup was derived from present experimental databank and from data obtained in literature. The databank's liquid viscosity ranges from 0.189 to 8.0 Pa s. Statistical analysis of the new correlation vis-à-vis existing ones showed that the present correlation gave the best performance with an average percent error, E 1 ; absolute average percent error, E 2 and standard deviation, E 3 of 0.001, 0.05 and 0.07 respectively, when tested on the high viscosity liquid–gas databank. Highlights: Experimental investigation of slug liquid holdup in high viscosity oil-gas two-phase flow in horizontal pipes is presented. Existing slug liquid holdup correlations are compared with the present experimental dataset. A new correlation for estimating slug liquid holdup is proposed. The proposed correlation is based on a databank with a wide range of liquid viscosity (0.189–8.090 Pa s).